Climate change effects on early stages of Quercus ariifolia (Fagaceae), an endemic oak from seasonally dry forests of Mexico - Badano, Ernesto I.; Guerra-Coss, Francisco A.; Sánchez-Montes de Oca, Erik J.; Briones-Herrera, Carlos I.; Gelviz-Gelvez, Sandra M. (Instituto de Ecología, A.C., 2019)
Background and Aims: Tree recruitment in seasonally dry forests occurs during the rainy season. However, higher temperatures and reduced rainfalls are expected in these ecosystems because of climate change. These changes could induce drought conditions during the rainy season and affect tree recruitment. Plants subjected to thermal or water stress often display morphological and physiological shifts addressed to prioritize their survival. If recently emerged tree seedlings display these responses, this could improve their development during the rainy season and increase their survival chances. Our aim was to test whether recently emerged oak seedlings display these responses.Methods: We performed a field experiment with Quercus ariifolia, an oak species endemic to seasonally dry forests of central Mexico. At the beginning of the rainy season (September 2016), we sowed acorns of this species in control plots under the current climate and plots in which climate change was simulated by increasing temperature and reducing rainfall (CCS plots). Seedling emergence and survival were monitored every seven days during the rainy season (until January 2017). At the end of the experiment, we measured several functional traits on surviving seedlings and compared them between controls and CCS plots.Key results: Higher temperature and lower rainfall generated water shortage conditions in CCS plots. This did not affect emergence of seedlings but reduced their survival. Seedlings that survived in CCS plots displayed shifts in their functional traits, which matched with those of plants subjected to thermal and water stress.Conclusions: Our results suggest that climate change can increase the extinction risk of Q. ariifolia in seasonally dry forest of Mexico by reducing the survival of its offspring. Nevertheless, the results also suggest that seedlings developed under climate change conditions can display functional shifts that could confer them tolerance to increased drought.